(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This article analyzes the current state of financing family entrepreneurship in Uzbekistan and the participation of commercial banks in this process. The study examined banking services, lending mechanisms and financial instruments aimed at supporting family business entities. The volume, terms and effectiveness of loans provided by commercial banks were also assessed. The analysis identified problems in the sector, including barriers to obtaining credit, collateral requirements and the level of financial literacy. The article develops proposals and recommendations for improving the activities of commercial banks in order to eliminate these problems and further develop family entrepreneurship. The results of the study have scientific and practical significance in improving the system of financing family entrepreneurship and strengthening the role of the banking sector.